2010
DOI: 10.1155/2010/539461
|View full text |Cite
|
Sign up to set email alerts
|

IL23RandIL12BSNPs and Haplotypes Strongly Associate with Crohn's Disease Risk in a New Zealand Population

Abstract: DNA samples from 339 Crohn's disease (CD) and 407 randomly selected controls from the Auckland (New Zealand) IBD project, were genotyped for five common single nucleotide polymorphisms in IL-23R (rs11805303, rs7517847, rs1343151, rs11209026, and rs10889677) and two in IL-12B (rs1363670 and rs6887695). While the IL-12B variants did not show an overall association and other IL23R variants led to minor changes in the risk of CD, rs1343151 and/or rs7517847 variants in the IL-23R gene strongly reduced the risk of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 42 publications
2
30
2
1
Order By: Relevance
“…In humans, IL-23 is over-expressed in clinical samples of psoriasis (Lee et al 2004), CD (Schmidt et al 2005) and ankylosing spondylitis (Wang et al 2009). Becker et al (2006) showed that blocking the p40 subunit of either IL-12 or IL-23, but not blocking the p19 unit (Ferguson et al 2010), was effective in reducing disease symptoms in chemically-induced colitis models. They suggested that there is a pre-disposition to IL-23-induced chronic inflammation in the terminal ileum.…”
Section: Il-23 (Interleukin Il-23)mentioning
confidence: 99%
See 3 more Smart Citations
“…In humans, IL-23 is over-expressed in clinical samples of psoriasis (Lee et al 2004), CD (Schmidt et al 2005) and ankylosing spondylitis (Wang et al 2009). Becker et al (2006) showed that blocking the p40 subunit of either IL-12 or IL-23, but not blocking the p19 unit (Ferguson et al 2010), was effective in reducing disease symptoms in chemically-induced colitis models. They suggested that there is a pre-disposition to IL-23-induced chronic inflammation in the terminal ileum.…”
Section: Il-23 (Interleukin Il-23)mentioning
confidence: 99%
“…The frequency of a functional single nucleotide polymorphism (SNP) in the IL-23 receptor gene (IL-23R; rs11209026, 1142 G wild-type A reduced function, Arg381Gln, R381Q) is significantly higher among healthy controls than in patients, suggesting a protective effect of the rare allele from immune-mediated chronic inflammation. The SNP rs11209026 encodes an amino acid change (Arg381Gln) in the protein product and has functional consequences; thus, R381Q is a causal variant (Ferguson et al 2010). This variant is a noncoding variant together with other genetic markers located in the IL23R gene (in exon 9 and coding for IL23R intra-cytoplasmic tail) and in its downstream intergenic region was identified as exerting a potent protective effect against IBD susceptibility.…”
Section: R381q Polymorphisms In the Il-23r Genementioning
confidence: 99%
See 2 more Smart Citations
“…This SNP was already reported to be associated with the susceptibility for CD and to be associated with ileal location in New Zealand population [44]. Multiple SNPs showing an association with both CD and UC have been identified in the IL23R gene by recent GWA studies.…”
Section: Discussionmentioning
confidence: 80%